2010
DOI: 10.14267/veztud.2010.07.02
|View full text |Cite
|
Sign up to set email alerts
|

A piaci normák sérülése, üzleti döntések és a vállalati hatékonyság (Violation of market norms, business decisions and firms’ efficiency)

Abstract: Az üzleti vállalkozások környezetére vonatkozó előfeltevések és ezek érvényesülése keretet szab az üzleti döntésekhez és hat a teljesítményre. A cikkben (a feltételezett, illetve elvárt) piaci normák sérülésének hatékonysági következményeit vizsgálja a szerző. Kiindulásként értelmezi a vállalati hatékonyság fogalmát és külső befolyásoló tényezőit. Ezt követően rendszerezi a nem normasértő üzleti döntéshozók lehetséges válaszait a piaci szereplők (versenytársak, üzleti partnerek) normasértéseire, kitérve arra i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, according to Lam (2012), if it falls only slightly below the 0.5 threshold, but at the same time the value of CR meets the expected value level (0.6), the convergence of the measurement variables towards the latent variable is acceptable (that is, our indicators/scales measure the latent variable for which they are intended). Presumably, convergence was compromised in this case because there is a behavioural element among the measurement variables (the company conducts or participates in a social responsibility project) and a statement relating to two values, and as a result of the contradiction between the values perceived and followed, there is a dissonance between the measurement variables according (Wimmer, 2010). Based on the above, it can be concluded that the convergent validity of the holistic marketing concept model exists.…”
Section: Confirmatory Factor Analysis (Cfa)mentioning
confidence: 95%
“…However, according to Lam (2012), if it falls only slightly below the 0.5 threshold, but at the same time the value of CR meets the expected value level (0.6), the convergence of the measurement variables towards the latent variable is acceptable (that is, our indicators/scales measure the latent variable for which they are intended). Presumably, convergence was compromised in this case because there is a behavioural element among the measurement variables (the company conducts or participates in a social responsibility project) and a statement relating to two values, and as a result of the contradiction between the values perceived and followed, there is a dissonance between the measurement variables according (Wimmer, 2010). Based on the above, it can be concluded that the convergent validity of the holistic marketing concept model exists.…”
Section: Confirmatory Factor Analysis (Cfa)mentioning
confidence: 95%